Konsep Mutu Dan Kepuasan Pelanggan Dalam Pendidikan Islam Metode TQM (Total Quality Management) - Salamah, Atina; Sa’diyah, Maemunah (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
Islamic education is one of the important pillars in shaping the character and personality of students. However, to achieve optimal quality of education, a systematic and effective managerial approach is needed. Total Quality Management (TQM) is one approach that can be applied in Islamic education to improve the quality of education and customer satisfaction, which in this context are students, parents, and the community. This journal examines the application of TQM principles in Islamic education to improve the quality of learning and ensure the achievement of customer satisfaction with an approach based on continuous improvement, process management, and the involvement of all parties. This study uses a descriptive qualitative method that refers to library data and interview results. This study intends to understand the situation about what happened to the research subjects. This method aims to describe or explain in full the occurrence of various phenomena studied. The results of this study indicate that. The improvements that Al-Munawwaroh Middle School implements are consistent and ongoing improvements in each school year. The way to find out what customers want is by working with the school committee to become a mediator or convey messages or hopes from the community to the school.